Different Techniques of Surgical Left Atrial Appendage Closure and Their Efficacy: A Systematic Review - Mizar D'Abramo; Silvia Romiti; Sara Saltarocchi; Wael Saade; Flaminia Spunticchia; Noemi Bruno; Mariangela Peruzzi; Fabio Miraldi; Giacomo Frati; Ernesto Greco; Francesco Macrina; Paolo De Orchi; et al. (Reviews in Cardiovascular Medicine, 2023)
Background: Atrial fibrillation has been identified as an independent risk factor for thromboembolic events. Since 1948 different surgical techniques have described the feasibility and the rationale of left atrial surgical appendage closure. The aim of this systematic review is to evaluate the reported patency rates of different surgical techniques. Methods: This systematic review was conducted according to preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Two independent investigators searched the PubMed, Scopus, Web of Science, Cochrane Central Register of Controlled Trials, and OVID® (Wolters Kluwer, Alphen aan den Rijn, Netherlands) to identify relevant studies. Consecutively, a PICO (Population, Intervention, Comparison and Outcomes) strategy assessment of literature was performed to search eventual other relevant studies that may have been ignored. Results: A total of 42 studies were included in our analysis. The total number of patients who underwent surgical left atrial appendage closure was 5671, and in 61.2% an imaging follow up was performed, mostly with transesophageal echocardiographic evaluation. Success rate for the different techniques was: Clip deployment 98%; Lariat procedure 88%; Surgical amputation 91%; Endocardial suture 74.3%, Epicardial suture 65%; Left atrial appendage closure (LAAC) ligation 60.9%; Stapler technique with excision of left atrial appendage (LAA) 100%; Stapler without excision 70%. Conclusions: To date, data on surgical left atrial appendage closure are poor and not standardized, even if reported rates are acceptable and comparable to transcatheter procedures. If validated on large-scale non-retrospective and multicentric studies, these promising developments may offer a valuable alternative for patients with atrial fibrillation (AF) and ineligible for oral anticoagulation therapy.